Investigating the effect of Individual Characteristics on Marketing Intelligence in Organization (Case Study: Tehran Scientific Centers and Manufacturing Companies) - M. Fariabi; A. Jalali Kalde; F. Nikbakht (تحقیقات بازار یابی نوین, 2011)
Nowadays, organizations are facing with plenty of environmental changes like never before. The changes take place promptly, that if organizations do not prepare themselves for facing with such changes their survival will be threatened. One of the very new tools that help organizations to reach a worthy position is the use of marketing intelligence. As there is no comprehensive conception of marketing intelligence in Iran, it is assumed as the synonymous of marketing information and market researches in many several books as well as scientific societies of our country. Therefore, the main purposes of this study are to develop the marketing intelligence theories and to specify effective individual characteristics on marketing intelligence in order to accomplish a stable competitive advantage. Accordingly by reviewing the literature review, a set of indicators relevant to each of the effective individual factors on marketing intelligence was collected, also the data was collected by questionnaire and interview. It is noteworthy that both qualitative and quantitative methodology were applied for the purpose of data analysis. The result of the research indicates that individual characteristics including character, creativity, motivation, intelligence, and organizational position are effective factors for making marketing intelligence.